Breach of information duties in the B2C e-commerce: a comparative analysis of English and Spanish law - Bednarz, Zofia (UMA Editorial, 2017)
B2C e-commerce is characterised by the information asymmetry between the contracting parties. Various information duties are imposed on traders, both at the European and national level to correct this asymmetry and to ensure proper market functioning. Nevertheless, there is no clear list of remedies for breach of information duties neither in national nor European law. Apart from few exceptions, where remedies for breach of certain information requirements are directly established, consumers need to claim remedies set out in the national law, within the specific provisions of consumer law, as well as general private law. The present study compares remedies for breach of information duties available in two European legal systems, English and Spanish, thus examining solutions adopted in common and civil law. The starting point for the analysis is the different approach to the mandated disclosure that each system developed: English law treats information duties with scepticism, whilst in Spanish law the principle of pre-contractual good faith governs the relationship of the parties, who are required to provide each other with relevant information. There are two types of information requirements that need to be considered: direct information duties established in lists enumerating information items to be provided, and indirect duties, which can be deduced from less specific provisions, often such that establish negative consequences of failure to provide information.The remedies for both types of duties in both legal systems analysed often overlap, which leads to a rather chaotic scheme of private redress for breach of information duties.
In the study various remedies are examined: remedies directly established in the legislation, such as the withdrawal period extension or consumer not being bound by the contract, remedies for indirect duties resulting from application of the specific consumer legislation: the regime of lack of conformity of the product with the contract and private redress for misleading commercial actions (specific to the English law), and finally remedies resulting from general private law, mainly defects of consent and breach of contract. Nevertheless, since the economics of general contract law differ importantly from principles of consumer e-commerce, various problems can be associated with the application of general law remedies to the breach of information duties in B2C contracts. The shortcomings of the current status quo of consumer protection through information duties from the perspective of their breach are presented, and various possible improvements are explored.
Keywords: Comercio electrónico - Contratos y especificaciones - Tesis doctorales; Information duties; Breach of information duties; B2C e-commerce; Consumer contract law; Comparative law